Genetic investigation of dementias in clinical practice - Takada, Leonel Tadao (Arquivos de Neuro-Psiquiatria, 2022)
Background: The field of neurodegenerative dementia genetics has advanced significantly over the past two decades, but there are still more to be discovered (such as the gene mutation in some familial forms of dementia). Objective: To provide a brief review of the most recent discoveries regarding monogenic dementia, and covering the most frequent genetic diseases that can cause dementia (neurodegenerative or not). Methods: A review of the literature will be carried out. Results: Neurodegenerative dementias, vascular dementias and leukoencephalopathies caused by single pathogenic variants are presented. Conclusion:  The spectrum of clinical presentations for most of the genes discussed is wide, and hence genetic testing in clinic should try to cover as many genes as possible.
Keywords: Alzheimer Disease; Frontotemporal Dementia; Genetic Testing; Dementia, Vascular; Leukoencephalopathies